VD_FINDINFO Arrêt / 2019 / 1075 vom 21. November 2019 - VD Tribunal cantonal (2019)
RÉVISIONDÉCISION, RÉVISIONPRESTATION D'ASSURANCE, DEGRÉ DE L'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ | 28 LAI, 4 LAI, 17 LPGA, 6 LPGA, 7 LPGA, 8 LPGA